2022
DOI: 10.3390/jcm11123399
|View full text |Cite
|
Sign up to set email alerts
|

Andexanet Alfa for Reversal of Factor Xa Inhibitors in Intracranial Hemorrhage: Observational Cohort Study

Abstract: Background: Intracranial hemorrhage (ICH) is associated with high mortality and morbidity, especially in patients under anticoagulative treatment. Andexanet alfa (AA) is a modified recombinant form of human factor Xa (FXa) developed for reversal of FXa-inhibitors, e.g., in the event of ICH, but experience is still limited. Methods: This monocentric retrospective observational cohort study included 46 patients with acute FXa-inhibitor-associated non-traumatic ICH (FXa-I-ICH) of whom 23 were treated with AA with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…However, more patients in the andexanet alfa group died or received palliative care (43.5%) versus the usual care group (26.1%). 18 The mortality rates in this trial were similar to what we found in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, more patients in the andexanet alfa group died or received palliative care (43.5%) versus the usual care group (26.1%). 18 The mortality rates in this trial were similar to what we found in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The mortality seen in our study is similar to the morality seen in the trial by Xian and colleagues, 17 where approximately 27% of ICH patients on a factor Xa inhibitor experienced mortality. Overall, 910 of 9202 (53.4%, proportion modified due to missing values) ICH patients taking a factor Xa inhibitor prior to admission received treatment with a prothrombin complex concentrate in the trial by Xian et al Rauch et al 18 compared treatment with andexanet alfa to usual care, including PCC, in patients with factor Xa inhibitor-associated ICH. In the 23 patients with an ICH due to a factor Xa inhibitor, 6 of 23 (26.1%) in the usual care group had ICH volume expansion greater than 33%, compared with 0% with andexanet alfa.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Most of these studies have been single-arm, single-center, or both. 6,7,11,12,16,[27][28][29][30][31][32][33][34][35] Some use historical rather than contemporary controls, or at best indirectly compared two independent datasets trying to account for major baseline differences by using a suboptimal PSM. 13 Other studies used propensity score treatment weighting rather than PSM and were able to account for bleed size/volume, which was not captured in the ORANGE indirect comparison.…”
Section: Discussionmentioning
confidence: 99%